DEPRESSION IN YOUNG ADULTS: FREQUENCY OF DEPRESSION AMONG YOUNG ADULT POPULATION - Muhammad Aslam Rind1 , Jeando Khan Daidano2 , Muhammad Saleem Rind3 , Haresh Kumar4 , Fahadul Zain5 , Safdar Ali Pervez Tunio6 . (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
ABSTRACT: INTRODUCTION: Depression associated with low energy and mood, affecting self-esteem, feelings and patients behavior. OBJECTIVE: We will determine the frequency of depression among young adult population. TYPE OF STUDY: Cross Sectional. DURATION OF STUDY: This study was conducted at psychiatric OPD LUMHS Hospital jamshoro from May 2019 to December 2020. METHODS: 110 patients were enrolled for this study. Out of 110 patients 62 were females and 48 were males, with patient permission depression was analyzed by using Beck Depression Inventory. Assessment of Depression was done by Beck Depression Inventory and Statics by software 15 version. RESULTS: Age ranged from 19-37 years, 51 male and 59 female. Occupation of the participants 27 farmers, 44 housewives, 17 unemployed, 13 self-employed, 7 Government Employ and 2 were Landlords. Depression level mild in 6 participants, border line clinical depression in 31 participants, moderate depression in 54 participants and severe depression in 19 participants CONCLUSION: Depression in young adults in severity presents with poor outcome, commonly seen in families with first and second degree relatives with previous history of depression. Depression is complicated by drug addiction. Treatment with antidepressant drugs, change in life style and psychotherapy patient can be prevented from complications.